Profil Kemampuan Berpikir Kritis Siswa pada Materi Pencemaran Lingkungan Ditinjau Dari Self Confidence - Purnomo, Muhammad Nurul; Hadi, Wiwin Puspita; Hidayati, Yunin; Muharami, Laila Khamsatul; Rosadi, Irsad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to identify the profile of students’ critical thinking skills on environmental pollution material in therm of self confidence. The study used a mixed type of research (mix method) with an explanatory sequential model conducted on students of SMP Negeri 1 Sumenep with a total population of all seventh grade students of SMP Negeri 1 Sumenep and a total sample of 16 students for the 2020/2021 academic year. The sampling technique is done by purposive sampling technique. Data were collected through test techniques, questionnaires, interviews, and documentation. The research data was obtained from the analysis of students' answers to the critical thinking ability test in terms of self-confidence. Indicators of critical thinking skills used are providing simple explanations, building basic skills, drawing conclusions, providing further explanations and developing strategies and techniques. The results showed that: 1) The critical thinking ability of students with low criteria was 3 students, moderate criteria were 2 students, and high criteria were 11 students. So, it can be concluded that students' critical thinking skills tend to be diverse with the category of critical thinking skills with high criteria being the most dominating ability. 2) Self confidence 9 students have a high level of self confidence, 6 students have a moderate level of self confidence, and 1 student has a low level of self confidence. So, it can be concluded that the students' self-confidence ability is dominated by having very good self-confidence.